Long-term nifedipine CR therapy and arterial characteristics in hypertensive patients aged over 60 years - V. E. Oleynikov (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To study arterial structure and function in patients aged over 60 years with Stage I-II isolated systolic and systolo-diastolic arterial hypertension (ISAH, SDAH). To assess vasoprotective effects of 24-week treatment with a calcium antagonist nifedipine (Cordaflex® RD).Material and methods. This prospective 24-week study included 48 patients with Stage I-II AH, aged over 60 years. SDAH and ISAH patients were administered Cordaflex® RD (40 mg/d), and treatment effectiveness was assessed by office blood pressure (BP) dynamics. Vasoprotective effects of the medication were assessed by volume sphyg-mography and echocardiography dynamics.Results. Cordaflex® RD demonstrated not only good antihypertensive effects, but also improved arterial elasticity, reducing pulse wave velocity (PWV) in various vessel types. In ISAH patients, its effects were maximal for elastic type vessels, and in SDAH individuals - for muscular type vessels. The medication reduced intima-media thickness (IMT) increase and improved endothelial function.Conclusion. In ISAH and SDAH patients aged over 60 years, Cordaflex® RD improved endothelial function and arterial wall elasticity, providing vasoprotection and target BP level achievement